Jawabanmu

2014-04-26T11:47:15+07:00
X cos²x=x(1-sin²x)=x-sinx.sinx²
f(x) = tan x . sin x
f'(x) = (sec² x) . (sin x) + (tan x) (cos x)
f'(x) = [sin x / cos² x] + [(sin x / cos x) . cos x]
f'(x) = [sin x / cos² x] + sin x
f'(x) = [sin x + sin x cos² x] / cos² x]
f(x) = [sin x (1 + cos² x)] cos² x
Komentar sudah dihapus
jawabannya jadi berapa mas?
cos²(x) - 2x sin(x) cos(x)
jalannya?
2014-04-26T14:35:54+07:00
Kalau ga salah -2sinx
salah lagi -_-
-2xsinx
salah :v
jadi jawabannya apa? -_-
cos²(x) - 2x sin(x) cos(x)